Prevalence and pattern of medico-legal cases in emergency department of a tertiary care Centre in Kathmandu, Nepal - Bharati, Urmila; Regmi, Upashana (Nepal Medical College Journal, 2023)
Medico-legal cases are essential component of medical practice and comprise important cases in emergencies.The objectives of this study was to assess the frequency and pattern of medico-legal cases and to identify the vulnerable gender, age group, outcome and the duration of stay in the Emergency Department of Nepal Medical College Teaching Hospital in Kathmandu. Medico-legal cases visiting emergencies from 1st March 2020 to 28th February 2021 were recorded using a proforma. During this period, a total of 1,176 medico-legal cases were registered (10.5% of the total emergency attendance; n=11,212) with 68.0% males and 32.0% females. Maximum number of cases belonged to the age group of 21 - 30 years (n=378; 32.1%) followed by 31 - 40 years (n=271; 23.0%). Most common medico-legal diagnosis was physical assault (n=389; 33.1%) followed by road traffic accidents (n=379; 32.2%). Majority of cases were accidental in nature (47.5%). Most of cases (56.1%) were discharged, 13.8% cases were admitted in different specialties for further management, 8.3% cases were referred to other centers and 21.7% cases left against medical advice. The length of stay was 15 minutes to 24 hours (mean 2.58 hours, SD 1.61). Most of the cases needed surgical consultation.